In vivo Digestibility in sheep fed with silage and supplemented with wheat bran, with the addition of Saccharomyces cerevisiae (Revista Sistemas de Producción Agroecológicos, 2025)
The requirements of sheep include water, energy, proteins, minerals and vitamins, which are essential to ensure proper growth, production and reproduction. These requirements vary according to the production system, physiological state, sex, age and live weight of the animal. However, the productivity of grazing sheep is limited by two main factors: the quality of the available forage and the high incidence of gastrointestinal parasites. In this research, an in vivo digestibility study was conducted with adult female sheep, with an average weight of 24.5 ± 8 kg, at the Universidad de los Llanos in the city of Villavicencio, Colombia. The objective was to develop sheep feeding strategies that incorporate agro-industrial by-products with high nutritional value, acting as energy-protein correctors in low-quality diets, in order to improve production rates. For the study, a 4x4 Latin square experimental design was used, applying four treatments to four animals during four periods. Each period consisted of four days of accustoming and three days of experimental data collection. The treatments evaluated were T1 = King Grass silage only (EK), T2 = EK + 6 gr probiotic (Saccharomyces cerevisiae), T3 = EK + 200 gr wheat bran (ST), T4 = EK + 200 gr ST + 6 gr probiotic. The variables evaluated were, digestibility coefficients (Cod) of nutrients such as: dry matter (DM), crude protein (PC), fat, crude fiber (FC), non-nitrogenous extract (ENN) with which total digestible nutrients (% TDN), digestible energy (DE in megacalories/k of DM) and metabolizable energy (ME in megacalories/k of DM) were calculated. The Cod of neutral detergent fiber (NDF) was also evaluated. Based on DM consumption, feed conversion (FC) was estimated. The results indicated that the four treatments had a similar performance, with numerically higher Cod of: DM, CP and fat in T2 (0.561, 0.875 and 0.895) and Cod of ENN and NDF in T1 (0.938 and 0.847 respectively). The Cod of FC, TDN, ED and EM were numerically higher in T4 (0.830, 64.97, 2.86 and 2.47 respectively). In the case of feed conversion and efficiency, the control represented a better performance, so it is concluded that the addition of supplements is not necessary when feeding these ruminants under these productive conditions.
Keywords: By-products; Forages; Probiotic; Ruminants